2007
DOI: 10.4049/jimmunol.179.10.6933
|View full text |Cite
|
Sign up to set email alerts
|

Inflammasome-Mediated Production of IL-1β Is Required for Neutrophil Recruitment against Staphylococcus aureus In Vivo

Abstract: IL-1R activation is required for neutrophil recruitment in an effective innate immune response against Staphylococcus aureus infection. In this study, we investigated the mechanism of IL-1R activation in vivo in a model of S. aureus infection. In response to a S. aureus cutaneous challenge, mice deficient in IL-1β, IL-1α/IL-1β, but not IL-1α, developed larger lesions with higher bacterial counts and had decreased neutrophil recruitment compared with wild-type mice. Neutrophil recruitment and bacterial clearanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
207
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 301 publications
(215 citation statements)
references
References 69 publications
8
207
0
Order By: Relevance
“…infection models. Our data are in general agreement with those from earlier studies showing that IL-1␤ promotes the production of neutrophil ERL CXC chemokines during acute inflammatory arthritis (38)(39)(40) and S. aureus-induced dermatitis (27). All together, the present study identifies a cytokine circuit whereby GBS-induced secretion of IL-1␤ stimulates resident tissue cells to produce ERL CXC chemokines.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…infection models. Our data are in general agreement with those from earlier studies showing that IL-1␤ promotes the production of neutrophil ERL CXC chemokines during acute inflammatory arthritis (38)(39)(40) and S. aureus-induced dermatitis (27). All together, the present study identifies a cytokine circuit whereby GBS-induced secretion of IL-1␤ stimulates resident tissue cells to produce ERL CXC chemokines.…”
Section: Discussionsupporting
confidence: 93%
“…We initially found that IL-1␤ is a fundamental, nonredundant factor for host resistance against GBS. These data extend to this pathogen the results of previous work on the importance of IL-1␤ or IL-1R in host defenses against other species of extracellular bacteria, such as Streptococcus pneumoniae and S. aureus (26)(27)(28)(29)(30). Next, we went on to study the mechanisms underlying the effects of IL-1␤ and focused on neutrophilic polymorphonuclear leukocytes for three reasons.…”
Section: Discussionmentioning
confidence: 55%
“…In addition, Hla activates the NLRP3 inflammasome in a variety of cells, resulting in the release of the inflammatory cytokine IL-1␤ (67,68,82). Although neutrophils and IL-1␤ are needed for the ultimate clearance of S. aureus SSTI (83,84), limiting inflammation caused by bacterial toxins clearly benefits the host.…”
Section: Discussionmentioning
confidence: 99%
“…These include extracellular pathogens, such as Streptococcus pneumoniae, Staphylococcus aureus, and Klebsiella pneumoniae (38)(39)(40), as well as intracellular bacteria, e.g., Listeria monocytogenes and Mycobacterium tuberculosis (41)(42)(43). Many papers describe the interaction of these pathogens with inflammasomes and the subsequent generation of IL-1␤ signals; these are summarized in recent reviews (44,45).…”
Section: Discussionmentioning
confidence: 99%